2013
DOI: 10.1111/j.1582-4934.2012.01661.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute hyperglycaemia enhances oxidative stress and aggravates myocardial ischaemia/reperfusion injury: role of thioredoxin‐interacting protein

Abstract: Hyperglycaemia during acute myocardial infarction is common and associated with increased mortality. Thioredoxin-interacting protein (Txnip) is a modulator of cellular redox state and contributes to cell apoptosis. This study aimed to investigate whether or not hyperglycaemia enhances Txnip expression in myocardial ischaemia/reperfusion (MI/R) and consequently exacerbates MI/R injury. Rats were subjected to 30 min. of left coronary artery ligation followed by 4 hrs of reperfusion and treated with saline or hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
59
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 46 publications
4
59
0
2
Order By: Relevance
“…Liu et al demonstrated that TXNIP-mediated NLRP3 inflammasome activation was involved in myocardial I/R injury [47]. Hyperglycaemia has been identified as an inducer of TXNIP expression in various cells including HK-2 [21, 22]; meanwhile, enhanced myocardial TXNIP expression that contributes to hyperglycaemia-aggravated oxidative stress and exacerbates cardiac injury following I/R has been reported [48]. TXNIP expression is markedly upregulated in human diabetes and diabetic complications [49, 50], indicating that TXNIP is a potential therapeutic target of diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al demonstrated that TXNIP-mediated NLRP3 inflammasome activation was involved in myocardial I/R injury [47]. Hyperglycaemia has been identified as an inducer of TXNIP expression in various cells including HK-2 [21, 22]; meanwhile, enhanced myocardial TXNIP expression that contributes to hyperglycaemia-aggravated oxidative stress and exacerbates cardiac injury following I/R has been reported [48]. TXNIP expression is markedly upregulated in human diabetes and diabetic complications [49, 50], indicating that TXNIP is a potential therapeutic target of diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Another candidate is p38 kinase. Recently, Su et al [42] have proved that hyperglycemia enhances myocardial TXNIP expression, possibly through reciprocally modulating p38 MAPK and Akt activation. According to their report, p38 kinase is located at the upstream of TXNIP, which is proposed by other groups [12].…”
Section: Discussionmentioning
confidence: 99%
“…Superoxide production in the tissues and cells was measured using lucigenin-enhanced chemiluminescence, as described previously [30] . Superoxide production was expressed as relative light units (RLU) per second per milligram heart weight (RLU·mg -1 ·s -1 ).…”
Section: Oxidative Damage Measurementmentioning
confidence: 99%
“…Superoxide production was expressed as relative light units (RLU) per second per milligram heart weight (RLU·mg -1 ·s -1 ). The MDA levels and the activities of the antioxidant SOD in the heart homogenates were determined spectrophotometrically, as previously described [30] .…”
Section: Oxidative Damage Measurementmentioning
confidence: 99%
See 1 more Smart Citation